1982
DOI: 10.1182/blood.v59.5.1046.bloodjournal5951046
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of bone marrow fibroblast colony-forming cells (CFU-F) and their progeny in patients with myeloproliferative disorders

Abstract: Chronic myeloproliferative disorders (MPD) are clonal diseases of the pluripotent hematopoietic stem cell frequently associated with myelofibrosis (MF). There is only indirect evidence indicating that the increased deposition of collagen in bone marrow matrix is a secondary phenomenon. A liquid culture system for cloning and growing bone marrow fibroblasts has permitted us to approach more directly the understanding of the pathogenesis of myelofibrosis by comparing the biophysical, growth, and functional chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The cell suspension was seeded into tissue culture flasks or plates at a density of 5 × 10 5 –1 × 10 6 cells/cm 2 , and in all comparisons, equal numbers of cells were used. After 3 days, nonadherent cells were removed, and the remaining adherent cells were refed twice weekly for colony‐forming assays [29] or establishment of primary cultures. Colonies containing >50 cells were selected using a cloning ring and single colony‐derived strains were passaged in α‐MEM + 15% FBS at confluency.…”
Section: Methodsmentioning
confidence: 99%
“…The cell suspension was seeded into tissue culture flasks or plates at a density of 5 × 10 5 –1 × 10 6 cells/cm 2 , and in all comparisons, equal numbers of cells were used. After 3 days, nonadherent cells were removed, and the remaining adherent cells were refed twice weekly for colony‐forming assays [29] or establishment of primary cultures. Colonies containing >50 cells were selected using a cloning ring and single colony‐derived strains were passaged in α‐MEM + 15% FBS at confluency.…”
Section: Methodsmentioning
confidence: 99%
“…If evidences are still lacking to attest the nonclonal nature of stromal cells in PMF, some data must be discussed. Cytogenetic-based analyses of bone marrow fibroblasts or MSCs isolated from PMF patients are ancient and based on low-sensitive technics [ 119 121 ]. Recently, some data suggested that MSCs from patients could display cytogenetic modification, before culture [ 122 ].…”
Section: Inflammation As a Keystone Of Bone Marrow Stroma Alteratimentioning
confidence: 99%
“…This is particularly evident in primary myelofibrosis (PMF) but is also associated with disease progression in all the other MPNs entities . Fibrosis of the bone marrow is considered as a secondary phenomenon in MPNs, as fibroblasts are not part of the environment in these disorders . The fibrosis in these cases is probably linked to abnormal production and release of several cytokines and growth factors by hematopoietic cells, especially dystrophic megakaryocytes of the malignant clone These cytokines and growth factors include platelet‐derived growth factor (PDGF), transforming growth factor beta, basic fibroblast growth factor, vascular endothelial growth factor and platelet factor‐4 (PF‐4).…”
Section: Introductionmentioning
confidence: 99%